(untitled) (AYUSHDHARA, 2025)
A cervical erosion is a condition in which the squamous covering of the vaginal aspect of the cervix is replaced by columnar epithelium which is continuous with that lining the endocervix. It is not an ulcer. Cervical erosion is typically manifested by heavy vaginal discharge (watery or whitish), contact bleeding and sometimes it may be associated with cervicitis. Its treatment is based on the principle of destruction of the columnar epithelium to be followed by its healing by the squamous epithelium. In Ayurvedic classics almost all the gynecological disorders come under the term Yonivyapad. It is best correlated with Karnini yonivyapad due to similarities in etiopathogenesis, clinical features and complications. This lesion is non-cancerous, but if not managed appropriately, it can contribute to infertility and may occasionally progress towards malignancy. In Ayurveda, Krnini yonivyapad can be treated with different treatment modalities like Yoni dhawana, Yoni pichu, Yoni varti, Ksharakarma, Agnikarma and the oral administration of the ayurvedic drugs. In this case study, patient with Karnini yonivyapada is treated with Panchvalkala kwatha yoni prakshalna followed by Jatyadi tailam yoni pichu one time daily for 10 days for consecutive two cycle and oral administration of ayurvedic medicine. The Yoni prakshalana and Yoni pichu in this case has showed the good results in improvement of Karnini yonivyapad.